Semiclassical quantization of spinning strings in AdS 4 × CP 3 - Alday, L; Arutyunov, G; Bykov, D (2008)
We derive the one-loop correction to the space-time energy of a folded string in AdS 4 × ℂℙ 3 carrying spin S in AdS 4 and angular momentum J in ℂℙ 3 in the long string approximation. From this general result in the limit J << log S we obtain the one-loop correction to the cusp anomalous dimension which turns out to be -(5log 2)/(2π). This value appears to be in conflict with the prediction from the recently conjectured all-loop Bethe ansatz. © SISSA 2008.